DGI-061 Safety of Triple Treatment in Chronic Hepatitis C. (12th March 2013) - Marrero, P; Lorente, L; Valero, S; Gil, I; Monte, E; Ruiz, J; Reig, J; Poveda, JL
Abstract : Background: Efficacy of chronic hepatitis C genotype 1 treatment has been improved with protease inhibitors (PIs) telaprevir and boceprevir. However, triple therapy (PI, peginterferon alfa and ribavirin) has increased the number, type and severity of adverse events. Purpose: To assess the safety of triple therapy in the first 12 weeks of treatment with telaprevir and boceprevir used for chronic hepatitis C treatment in clinical practise. Materials and Methods: Between March and September 2012, all patients treated with telaprevir and boceprevir receiving medicines in the outpatient pharmaceutical care unit of a tertiary hospital were interviewed. Adverse events were collected in a predefined questionnaire. Anaemia, neutropenia and thrombocytopenia were also included as adverse effects if the patient had been treated for any of them. Interviews were conducted during the medicines dispensing (monthly). Results: Fifty-one patients with triple therapy were interviewed; 34 of them were treated with telaprevir and 17 with boceprevir. All patients had at least one adverse event on any of the visits. Globally, the most frequent adverse events were tiredness (84.3%), digestive disorders (70.6%), dermatological disorders (64.7%) and influenza-like syndrome (62.7%). Patients being treated with telaprevir mainly suffered from tiredness (85.3%) and dermatological disorders (70.6%). However, tiredness (82.4%) and mood disorders (70.6%) were the most usual adverse events in patients being treated with boceprevir. The frequencies of other side effects are listed in Table 1. Conclusions: Efficacy in the first 12 weeks of triple therapy results in a high frequency of adverse events. Information on possible side effects and how to prevent or treat them is important for patients. Since PIs have only recently come onto the market, it is also important to communicate and record any new adverse events not identified in clinical trials. No conflict of interest.